Systemizing the Pedagogic Concepts - G. N. Serikov (Russian State Vocational Pedagogical University, 2015)
The paper emphasizes the necessity of systemizing the pedagogic concepts to complement the pluralism principle dominating in pedagogy over the recent years. The author recommends the person oriented systematic synergetic methodology combining various research data into a holistic scientific approach. The paper regards education as the core pedagogic concept - including training, upbringing, self-education, their respective subcomponents, and generated personal resource. The elements of personal resource combine the acquired knowledge, skills and values, developed subjective attitudes and individual health data. The key pedagogic terms describing the educational process are represented by a three-level system; the first level involves the educational form concepts, the second - generated personal resource, the third - summarized notion system combining the previous levels and reflecting their binary relations. The given construct systemizes the pedagogic conceptual apparatus and clarifies the theoretical notion of personal education.